2013
DOI: 10.4049/jimmunol.1300121
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD1d Restriction and Th1/Th2/Th17 Cytokine Secretion by Human Vδ3 T Cells

Abstract: Human γδ T cells expressing the Vδ3 TCR comprise a minor lymphocyte subset in blood but are enriched in liver and in patients with some chronic viral infections and leukemias. We analysed the frequencies, phenotypes, restriction elements and functions of fresh and expanded peripheral blood Vδ3 T cells. Vδ3 T cells accounted for ~0.2% of circulating T cells, included CD4+, CD8+ and CD4−CD8− subsets, and variably expressed CD56, CD161, HLA-DR and NKG2D, but not NKG2A nor NKG2C. Vδ3 T cells were sorted and expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 25 publications
1
139
0
Order By: Relevance
“…We also confirm a previous report (17) that C. albicans drives expansion and IL-17 production by human Vd1 T cells in vitro. We initially tested several protocols (30,31) for expanding Vd1 T cells and found that coculturing PBMCs enriched for gd T cells with DCs activated with the dectin-1 ligand curdlan in the presence of PHA and IL-2 resulted in the selective expansion of Vd1 T cells. Subsequently, it was found that substituting curdlan with heat-or ethanol-inactivated C. albicans, also known to bind dectin-1 (18)(19)(20), could similarly promote Vd1 T cell expansion in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also confirm a previous report (17) that C. albicans drives expansion and IL-17 production by human Vd1 T cells in vitro. We initially tested several protocols (30,31) for expanding Vd1 T cells and found that coculturing PBMCs enriched for gd T cells with DCs activated with the dectin-1 ligand curdlan in the presence of PHA and IL-2 resulted in the selective expansion of Vd1 T cells. Subsequently, it was found that substituting curdlan with heat-or ethanol-inactivated C. albicans, also known to bind dectin-1 (18)(19)(20), could similarly promote Vd1 T cell expansion in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A number of protocols for the ex vivo expansion of human gd T cells from healthy donors were tested (30,31), and the following method was optimized for generating lines of Vd1 T cells. PBMCs prepared from buffy coat packs were enriched for total gd T cells using Ab-coated magnetic beads and cultured for 7-14 d in medium containing PHA-L and IL-2, with monocyte-derived DCs that had been matured overnight with curdlan or heat-or ethanolkilled C. albicans ( Fig.…”
Section: Albicans Drives the Expansion Of Vd1 T Cells In Vitromentioning
confidence: 99%
“…Several studies have demonstrated CD1a, CD1b, CD1c and CD1d reactivity of human Vd1 + T cells [198][199][200][201][202][203] and CD1d-reactivity of human Vd3 + T cells [204]. Roles for CD1-restricted Vd1 + and Vd3 + T cells in the induction of adaptive immune responses are evident from studies that have shown that these cells can induce MHC and costimulatory receptor expression and cytokine production by DC, conferring upon DC the capacity to drive alloreactive T cell proliferation [204,205]. Additionally, one report described the ability of CD1-restricted Vd1 + T cells specific for pollen-derived phosphatidyl-ethanolamine to drive IgE production by B cells [200].…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%
“…Whilst Vc9/Vd2 T cells make up the majority of peripheral human cd T cells, Vd1 + and Vd3 + ('Vd2 neg ') T cells are the predominant cd T cell subtypes in human intestine and liver [196,197]. Several studies have demonstrated CD1a, CD1b, CD1c and CD1d reactivity of human Vd1 + T cells [198][199][200][201][202][203] and CD1d-reactivity of human Vd3 + T cells [204]. Roles for CD1-restricted Vd1 + and Vd3 + T cells in the induction of adaptive immune responses are evident from studies that have shown that these cells can induce MHC and costimulatory receptor expression and cytokine production by DC, conferring upon DC the capacity to drive alloreactive T cell proliferation [204,205].…”
mentioning
confidence: 99%
“…Vδ3 T cells are a minor population in the blood but are more dominant in the liver and in leukemic patients. Upon activation with IL-2, Vδ3 T cells are expanded and recognize CD1d and, thereby, can lyse CD1d + target cells and release cytokines such as IL-17 and IFN-γ (46). A substantial body of evidence now demonstrates that γδ T cells play a central role in defending the host against a wide range of infections as well as sterile stresses such as malignant transformation.…”
Section: γδ T Cells: Development Tissue Distribution and Functionmentioning
confidence: 99%